CXCR4 Mediates Enhanced Cell Migration in CALM-AF10 Leukemia - Fertal, Shelby A.; Zaidi, Sayyed K.; Stein, Janet L.; Stein, Gary S.; Heath, Jessica L. (Frontiers in Oncology, 2022)
Leukemia transformed by the CALM-AF10 chromosomal translocation is characterized by a high incidence of extramedullary disease, central nervous system (CNS) relapse, and a poor prognosis. Invasion of the extramedullary compartment and CNS requires leukemia cell migration out of the marrow and adherence to the cells of the local tissue. Cell adhesion and migration are increasingly recognized as contributors to leukemia development and therapeutic response. These processes are mediated by a variety of cytokines, chemokines, and their receptors, forming networks of both secreted and cell surface factors. The cytokines and cytokine receptors that play key roles in CALM-AF10 driven leukemia are unknown. We find high cell surface expression of the cytokine receptor CXCR4 on leukemia cells expressing the CALM-AF10 oncogenic protein, contributing to the migratory nature of this leukemia. Our discovery of altered cytokine receptor expression and function provides valuable insight into the propagation and persistence of CALM-AF10 driven leukemia.